2019
DOI: 10.1186/s12879-019-4072-6
|View full text |Cite
|
Sign up to set email alerts
|

“It depends how one understands it:” a qualitative study on differential uptake of oral cholera vaccine in three compounds in Lusaka, Zambia

Abstract: Background The Zambian Ministry of Health implemented a reactive one-dose Oral Cholera Vaccine (OCV) campaign in April 2016 in three Lusaka compounds, followed by a pre-emptive second-round in December. Understanding uptake of this first-ever two-dose OCV campaign is critical to design effective OCV campaigns and for delivery of oral vaccines in the country and the region. Methods We conducted 12 Focus Group Discussions (FGDs) with men and women who self-reported taking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 39 publications
(35 reference statements)
0
6
0
2
Order By: Relevance
“…Rationale for selection of qualitative method : The selected articles provided a broad range of reasons for the use of qualitative methods. These included the need to generate formative insights to influence the design of programmes, such as vaccinations, childhood feeding, Ebola and malaria control, 52–54 , 66 , 68 , 71 , 76 to increase community and stakeholder participation, including with racial and ethnic minority communities in HIV/AIDS prevention, 70 injecting drug users 73 and those undergoing aortic valve implants, 56 and to understand specific operational shortcomings or failures of accepted approaches and policies, many of which were comparative studies reflecting on implementation across multiple countries. 58,60 , 61 , 75 …”
Section: Resultsmentioning
confidence: 99%
“…Rationale for selection of qualitative method : The selected articles provided a broad range of reasons for the use of qualitative methods. These included the need to generate formative insights to influence the design of programmes, such as vaccinations, childhood feeding, Ebola and malaria control, 52–54 , 66 , 68 , 71 , 76 to increase community and stakeholder participation, including with racial and ethnic minority communities in HIV/AIDS prevention, 70 injecting drug users 73 and those undergoing aortic valve implants, 56 and to understand specific operational shortcomings or failures of accepted approaches and policies, many of which were comparative studies reflecting on implementation across multiple countries. 58,60 , 61 , 75 …”
Section: Resultsmentioning
confidence: 99%
“…A previous qualitative study from Mozambique displayed hesitancy towards oral cholera vaccination and recommended the promotion of community engagement in the trust building efforts aiming to address cholera epidemic [ 59 ]. Another study from Zambia recommended the provision of transparency about cholera vaccine effectiveness and possible side effects to promote vaccine uptake and to tackle the possible conspiratorial beliefs regarding the vaccine [ 60 ]. Furthermore, two studies from Tanzania showed the importance of trust in health systems, optimal vaccine campaign implementation, and providing vaccination for free as cholera vaccine acceptance declined if payment was needed as determinants for cholera vaccine uptake [ 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tanzania also has low compliance with HPV screening as part of the battle against cervical cancer, mainly because of a lack of confidence in provision for diagnosis and treatment (Urasa and Darj 2011). As Heyerdahl and Pugliese-Garcia note: Despite universal provision, evidence suggests relatively low vaccination coverage in Zambia' (Babaniyi et al 2013;Heyerdahl et al 2019), with the result that, despite there being provision for universal coverage of vaccinations in Zambia since the 1970s, during 2013-2014 there was only a 60% vaccination take-up rate. A systematic study showed that the principal obstacles to full vaccine coverage in Zambia were a belief in traditional remedies, general aversion to injections and distance from medical centres.…”
Section: Religious and Politcal Factorsmentioning
confidence: 99%